The reliability and validity of a soccer-specific nonmotorised treadmill simulation (intermittent soccer performance test) - Aldous, J. W. F.; Akubat, I.; Chrismas, B. C. R.; Watkins, S. L.; Mauger, A. R.; Midgley, A. W.; Abt, G.; Taylor, L. (The Journal of Strength and Conditioning Research, 2014)
This study investigated the reliability and validity of a novel nonmotorised treadmill (NMT)-based soccer simulation using a novel activity category called a "variable run" to quantify fatigue during high-speed running. Twelve male University soccer players completed 3 familiarization sessions and 1 peak speed assessment before completing the intermittent soccer performance test (iSPT) twice. The 2 iSPTs were separated by 6-10 days. The total distance, sprint distance, and high-speed running distance (HSD) were 8,968 ± 430 m, 980 ± 75 m and 2,122 ± 140 m, respectively. No significant difference (p > 0.05) was found between repeated trials of the iSPT for all physiological and performance variables. Reliability measures between iSPT1 and iSPT2 showed good agreement (coefficient of variation: <4.6%; intraclass correlation coefficient: >0.80). Furthermore, the variable run phase showed HSD significantly decreased (p < 0.05) in the last 15 minutes (89 ± 6 m) compared with the first 15 minutes (85 ± 7 m), quantifying decrements in high-speed exercise compared with the previous literature. This study validates the iSPT as a NMT-based soccer simulation compared with the previous match-play data and is a reliable tool for assessing and monitoring physiological and performance variables in soccer players. The iSPT could be used in a number of ways including player rehabilitation, understanding the efficacy of nutritional interventions, and also the quantification of environmentally mediated decrements on soccer-specific performance.